RESULTS OF EMERGENCY LAPAROSCOPIC CHOLECYSTECTOMY IN PATIENTS WITH HIGH OPERATIONAL RISK - F.I. MAKHMADOV; D. MIRBEGIEV; P.SH. KARIMOV; KH.SH. MAKHMADYOROV (Avicenna Tajik State Medical University, 2019)
Objective: To study the results of emergency laparoscopic and traditional cholecystectomy in patients with high operational risk. Methods: The results of surgical treatment of 132 patients with acute calculous cholecystitis with high operational risk were studied, in particular: advanced age - 34.8% (n=46); Grade III-IV obesity - 24.3% (n=32); history of abdominal operations - 18.2% (n=24); "difficult" gallbladder - 22.7% (n=30). Conducted clinical, laboratory and instrumental methods of research. In 89 (67.4%) cases, emergency laparoscopic cholecystectomy (LCE) was performed, in 43 (32.6%), emergency traditional cholecystectomy was performed. Results: All urgent LCEs are distributed according to the degree of complexity according to the classification of LCE classes according to Iannet. Not one of the interventions, of the main group of patients did not correspond to the "simple" class of LCE. 87 (97.8%) cases were related to "complex" LCE when technical difficulties arose at different stages of the operation: with the imposition of pneumoperitoneum and the installation of trocars in patients with obesity (n=24) and with the adhesive disease after suffered abdominal operations (n=16). "Dangerous" LCE was noted in 2 (2.2%) cases of Mirizzi type II syndrome, which required conversion with intraoperative choledochoscopy. In 43 observations, an open cholecystectomy was produced, of which, in 62.6% of cases non-standard techniques have been implemented: Pribram cholecystectomy (n=11), "from the bottom" (n=5) and the "piece-breaking" method (n=5). After performing open interventions, 7 (16.3%) patients experienced postoperative complications with a lethal outcome (2.3%). In LCE, complications were observed in 11.2% of cases in the form of bleeding from the gallbladder bed (n=6) and bile leakage through the control drainage (n=4). In the postoperative period after LCE, one patient (1.1%) died of pulmonary embolism. Conclusion: The application of the proposed techniques allows reducing the duration of the operation, reducing the number of intra- and postoperative complications and, thereby, improving the results of surgical treatment of this heavy contingent of patients.